The Role of Gesture in Social Telepresence Robots—A Scenario of Distant Collaborative Problem-Solving - Anastasiou, Dimitra; Stahl, Christoph; Latour, Thibaud (Social Robots: Technological, Societal and Ethical Aspects of Human-Robot Interaction, 2019)
Human–robot interaction is a well-studied research field today; robots vary from tele-operators and avatars to robots with social characteristics. In this review paper, first we present related work on tele-operation, mobile robotic telepresence, and Social robots. Then, we focus on the role of gestures and body language in robotics, and more precisely their importance for communication in collaborative settings. In our collaborative setting scenario, we have a group of multiple human users working on Collaborative Problem-Solving-solving around a tangible user interface (TUI). A TUI employs physical artifacts both as “representations” and “controls” for computational media. We have the same situation in a separate spatial location. We extend this specific scenario by having an avatar robot in each one of the two locations which represents remote team members and mirrors their actions, gaze, and gestures. Our goal in this paper is to give an overview of current solutions that provide a sense of being in a different place and to describe our future scenario of having an avatar robot solving a problem on a TUI collaboratively with human users. We present a discussion about technical and social questions related to the acceptance of avatar robots at work considering which properties they should have, to what extent the current state of the art in social robotics is applicable, and which additional technical components need to be developed.